Discrepancia hueso-diente en pacientes atendidos en una consulta de Ortodoncia - Cordero Santos, Yeiny; Nuñez Peña, Lian Cristino; Socarrás Laguna, Yadira; Castañeda Cruz, Yusmara (Revista Electrónica Dr. Zoilo E. Marinello Vidaurreta, 2025)
Introduction: the analysis of study models for the identification of bone-tooth discrepancies is an essential diagnostic tool in orthodontic diagnosis. Objective: to epidemiologically and clinically characterize bone-tooth discrepancies in patients seen in an orthodontic practice. Method: a cross-sectional, descriptive, observational study was conducted in the Orthodontic Department of the 3 de Octubre Teaching Clinic in Las Tunas province from January 2021 to December 2024. The population consisted of 1,580 patients and a sample of 150 children treated in the previous five years. The variables studied were age, sex, clinical manifestations, bone-tooth discrepancy, and the severity of the negative bone-tooth discrepancy. Absolute and relative frequencies, standard deviation, chi-square, and the Pearson correlation coefficient were calculated with a significance level of 0.05. Results: female sex (63.3 %) and the 12-15 age group (46.7 %) were the most representative epidemiological parameters. Crowding and vestibuloversion of incisors with and without diastemas predominated in 65, 38, and 33 patients, respectively. Negative bone-tooth discrepancy predominated in 79 (52.7 %) patients in both jaws. Conclusions: the characteristic patient profile in the Orthodontic consultation corresponds to females aged 12 to 15 years, predominantly presenting with negative bone-tooth discrepancy. This condition manifests clinically as crowding and shows a strong correlation between the dental arches, reinforcing the need for a comprehensive treatment approach.